Analisis Spektral Daya dan Koherensi Sinyal Electroencephalography (EEG) Area Frontal Pada Pecandu Rokok - Handayani, Nita; Rahmah, Gebrina (Prodi Fisika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2021)
This study will discuss the characteristics of the frontal area brain electrical signals in cigarette addicts before and after smoking based on QEEG analysis. Several neuroimaging techniques are used to understand the relationships between brain functionality. Quantitative Electroencephalography (QEEG) is a non-invasive technique that can be used to provide an overview of brain functionality through several physical quantities being assessed. Recording of brain signals using Emotiv Epoc 14 electrodes and only focuses on 8 frontal area electrodes (AF3, F7, F3, FC5, FC6, F4, F8, AF4) and 2 reference channels. The number of test subjects in the study was 5 people, male with an age range between 20-25 years. Brain recording was done when the eyes were open, eyes closed, and the task was to do math problems. Data analysis methods include pre-processing of EEG data to remove noise and artifacts, calculation of spectral power using Welch's periodogram, and analysis of brain functional connectivity by calculating the amount of intra-hemisphere and inter-hemisphere coherence. The results of the analysis of the spectral power showed that before smoking an increase in the spectral power occurred at the delta and alpha wave frequencies, and a decrease occurred in the theta wave frequencies. Meanwhile, after smoking an increase occurred in the frequency of delta, alpha and beta waves and a decrease occurred in the frequency of theta waves. The coherence analysis results showed a significant difference in the coherence of the right intra-hemisphere of theta wave frequency and the inter-hemisphere coherence of beta wave frequencies before and after smoking.